Agama dalam Perspektif Sosiologis - Hamali, Syaiful (Universitas Islam Negeri Raden Intan Lampung, 2017)
In established societies, religion is an important social institutional structure, which complements all existing social systems and is interdependent with other parts, so that changing one part will affect other parts, ultimately affecting the entire social system in society. Sedamgkan religion is related to trust and its various problems to date have always been found in every society, including providing meaning, meaning and interpretations by scientific experts on social order in religious communities. Religion is marked as unifying the most sublinest human aspirations; as a sign of morality, as a source of community order and individual peace; as something that glorifies and makes human beings civilized. On the other hand religion is accused of being a barrier to progress, and heightens fanaticism and is intolerant, hostile, superstitious, heresy, and khurafat. But religion also shows its ability to give birth to very revolutionary tendencies in the fabric of people's lives, such as the 19th-century peasant uprising in Germany as a milestone in the early rise of human civilization.